Association of baseline parameters with year 0 and year 1 acute exacerbations in male patients with chronic obstructive pulmonary disease. (4th May 2022) - Chang, Yu-Ping; Chen, Yu-Mu; Chang, Ya-Chun; Liu, Shih-Feng; Fang, Wen-Feng; Chao, Tung-Ying; Wu, Chao-Chien; Chang, Huang-Chih; Lin, Meng-Chih; Chen, Yung-Che
Objectives: Acute exacerbations (AEs) of chronic obstructive pulmonary disease (COPD) can affect health status, hospitalization and readmission rates, and disease progression. This study aimed to identify independent markers associated with COPD AEs. Methods: This study included male patients with COPD and collected data regarding their AEs and baseline clinical parameters. Results: We included 149 male patients. Among them, 58 were included in the year 0 high-AE group and 91 in the low-AE group. Multivariate analysis revealed that the high-AE group had higher white blood cell count, lower serum albumin level, and post-bronchodilator (BD) forced expiratory volume in one second (FEV1 ) (%) with a combined receiver operating characteristic curve (ROC) of 0.721 ( p < 0.001). Additionally, 34 patients were included in the year 1 high-AE group and 70 in the low-AE group ( p < 0.001). Multivariate analysis revealed that the high-AE group had higher platelet count, positive asthma history, and lower pre-BD FEV1 (%) with a combined ROC of 0.782 ( p < 0.001). Conclusion: In male patients with COPD, baseline white blood cell count, albumin level, and post-BD FEV1 (%) were correlated with year 0 AE; on the other hand, baseline platelet count, positive asthma history, and pre-BD FEV1 (%) were associated with year 1 AE.